Urban flood resilience evaluation in China: a systematic review of frameworks, methods, and limitations - Long, Liu; Junjia, Yin; Jiao, Wang; Alias, Aidi Hizami; Haron, Nuzul Azam; Abu Bakar, Nabilah (Taylor and Francis, 2025)
With the acceleration of climate change and urbanization, the impacts of floods on Chinese cities have become increasingly severe, and improving urban flood resilience has become an urgent issue. Although scholars in China have proposed many methods to evaluate urban flood resilience in the last decade, research in this field has not been critically reviewed thoroughly and in detail. Therefore, this study selects high-quality original research papers from the previous decade and focuses on analyzing the location, framework, data, analytical methods, and limitations of current assessment methods. The study’s main objective is to inform the identification of a flood resilience assessment system applicable to the Chinese urban context while revealing the existing methodology’s shortcomings in data accuracy and quality, consideration of regional variability, and indicator validity. Finally, the study finds significant challenges in eight field areas: talent pool, public participation, and investment and financing mechanisms. It provides eight targeted strategies, such as building a multi-sectoral synergistic governance mechanism.